KV7 Channel Expression and Function Within Rat Mesenteric Endothelial Cells - Baldwin, Samuel N.; Sandow, Shaun L.; Mondéjar-Parreño, Gema; Stott, Jennifer B.; Greenwood, Iain A. (Frontiers in Physiology, 2020)
Abstract Background and purpose Arterial diameter is dictated by the contractile state of the vascular smooth muscle cells (VSMCs), which is modulated by direct and indirect inputs from endothelial cells (ECs). Modulators of KCNQ-encoded kv7 channels have considerable impact on arterial diameter and these channels are known to be expressed in VSMCs but not yet defined in ECs. However, expression of Kv7 channels in ECs would add an extra level of vascular control.. This study aims to characterize the expression and function of KV7 channels within rat mesenteric artery ECs. Experimental approach In rat mesenteric artery, KCNQ transcript and KV7 channel protein expression were determined via RT-qPCR, immunocytochemistry, immunohistochemistry and immunoelectron microscopy. Wire myography was used to determine vascular reactivity. Key results KCNQ transcript was identified in EC marker expressing cells using a reductive approach. KV7.4 and KV7.5 protein expression was determined in both isolated EC and VSMC and in whole vessels. Removal of ECs attenuated vasorelaxation to two structurally different KV7.2-5 activators S-1 and ML213. KIR2 blockers ML133, and BaCl2 also attenuated S-1 or ML213-mediated vasorelaxation in an endothelium-dependent process. KV7 inhibition attenuated receptor-dependent nitric oxide (NO)-mediated vasorelaxation to carbachol, but had no impact on relaxation to the NO donor, SNP. Conclusions and implications In rat mesenteric artery ECs, KV7.4 and KV7.5 channels are expressed, functionally interact with endothelial KIR2.x channels and contribute to endogenous eNOS-mediated relaxation. This study identifies KV7 channels as novel functional channels within rat mesenteric ECs and suggests that these channels are involved in NO release from the endothelium of these vessels.